Pengaruh Manajemen Kualitas Terhadap Kinerja Organisasi pada Usaha Kecil Menengah di Kota Metropolitan - Soliatun (MES Bogor, 2025)
This study aims to analyze the influence of quality management on organizational performance in Small and Medium Enterprises (SMEs) in a metropolitan city. Quality management, encompassing the planning, control, and improvement of product and service quality, is considered a crucial factor in achieving optimal organizational performance. This research employs a quantitative method with a multiple linear regression approach to test the proposed hypothesis. The research sample was taken from SMEs in a metropolitan city that meet specific criteria. The results show a significant influence between quality management and the organizational performance of SMEs. Improved implementation of quality management positively impacts increased organizational performance, including increased productivity, efficiency, and customer satisfaction. These findings have important implications for SMEs in enhancing their competitiveness in a competitive market. This study recommends that SMEs pay more attention to and improve the implementation of quality management to achieve better performance. The limitations of this study lie in the limited sample scope and the unconsidered external factors.